2021
DOI: 10.1039/d1ce00697e
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical treatment of quercetin and curcumin to obtain eutectic mixtures with high antioxidant activity

Abstract: Quercetin and curcumin are well-known natural antioxidant molecules used to prevent the malignant effect caused by free radicals on biological systems. This work addressed the creation of eutectic mixtures from...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Cocrystal formation could not be observed for the remaining selected coformers, despite the many attempts with different cocrystallization techniques (solution, slurry, or mechanochemical methods), stoichiometric ratios, solvents, and temperatures. In the end, we decided to investigate the phase diagrams of a small number of binary systems, to determine their eutectic composition and temperature: eutectic compositions are currently recognized as a possible alternative, when cocrystal formation is not possible, to modify the physical properties of a compound, such as thermal stability and solubility. We thus prepared via ball-milling (see Experimental Section) solid-state mixtures of HKA containing mole fractions from 0 to 1 of the second component of interest. DSC measurements were then performed, and the resulting thermograms (see Figures S14–S18) used for the construction of the binary phase diagrams (see Experimental Section).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Cocrystal formation could not be observed for the remaining selected coformers, despite the many attempts with different cocrystallization techniques (solution, slurry, or mechanochemical methods), stoichiometric ratios, solvents, and temperatures. In the end, we decided to investigate the phase diagrams of a small number of binary systems, to determine their eutectic composition and temperature: eutectic compositions are currently recognized as a possible alternative, when cocrystal formation is not possible, to modify the physical properties of a compound, such as thermal stability and solubility. We thus prepared via ball-milling (see Experimental Section) solid-state mixtures of HKA containing mole fractions from 0 to 1 of the second component of interest. DSC measurements were then performed, and the resulting thermograms (see Figures S14–S18) used for the construction of the binary phase diagrams (see Experimental Section).…”
Section: Results and Discussionmentioning
confidence: 99%
“…[3b] This strategy has been employed for constructing several co-crystals of CUR and QUER with multiple co-crystallizers such as trimesic acid, resorcinol, nicotinamide and others.. [11][12] In the first approach, our group generated a series of eutectic mixtures using equivalent quantities of CUR and QUER dihydrate under mortar and pestle mechanochemical conditions. [13] This study demonstrated that using eutectic mixtures increases anti-oxidant activity and thermal stability by up to 50 %, making this mixture a potential raw material in multiple cosmetic or pharmacological products. As a continuation of previous work and in the constant search for new co-crystal materials, the present work reports the syntheses of a new crystalline phase of the CUR : QUER mixture using a ball mill grinding mechanochemical technique.…”
Section: Introductionmentioning
confidence: 81%
“…[27] FRS 50 values obtained for the M3 and M8 co-crystals (5.700 and 7.0407 mg/L, respectively) and the eutectic mixtures (M1 = 5.5118 mg/L; M2 = 4.9388 mg/L; M4 = 9.8270 mg/L; M5 = 6.2051 mg/L; M6 = 6.7711 mg/L; M7 = 6.2446 mg/L; M9 = 6.0774 mg/Land M10 = 5.8441 mg/L) were similar to the previously reported values by our group (Mix 2, CUR : QUER eutectic mixture, ground using an agate mortar and pestle for 10 min). [13] Notably, the binary phases, whether co-crystals or eutectic, showed higher activity than the pure compounds of QUER (3.4441 mg/L), CUR oxidant activity in polyphenols proceeds mainly in two ways: i) hydrogen atom transfer (HAT) or ii) single electron transfer (SET); anti-oxidant mechanisms are related with the OÀ H bond energy and the ionization potential, respectively [28]. Generally, the polyphenols and curcuminoids are better HAT anti-oxidant, indicating that the anti-oxidant capacity is determined by how easy it is to take a hydrogen atom by the radical.…”
Section: Anti-oxidant Capacity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 The use of eutectics in pharmaceutical formulations is quite advantageous because (1) in a eutectic, the crystalline constituents make it more stable than its amorphous counterparts; (2) eutectics are easy to synthesize and scale up; and (3) because they are not considered new chemical entities, they do not require clinical trials. 5,11,16 Despite their enhanced critical properties related to product performance, such as solubility, stability, and bioavailability, organic eutectics have been relatively unexplored compared to salts and cocrystals. [17][18][19][20] This can be attributed to the limitations related to no tested empirical or theoretical tools to guide a priori discovery of organic eutectic composites.…”
Section: Introductionmentioning
confidence: 99%